Performance evaluation of photocatalytic fuel cell for simultaneous electricity generation and dyes degradation / \c Lee Sin Li. - Lee, Sin Li (School of Materials Engineering, Universiti Malaysia Perlis, 2018)
The research objectives are to fabricate and characterize the photoanodes by using different methods for application in photocatalytic fuel cell ; to evaluate the operating parameter that affect the efficiency of the photocatalytic fuel cell for simultaneous wastewater treatment and electricity generation ; to investigate the degradation pathway of azo dye Reactive Green 19 treated in photocatalytic fuel cell.